Customer-Centricity as a Core Value: Redefining Business Management for the Experience Economy - Kenaphoom, Sanya; Sriwapee, Kanokwan; Ruangchai, Netnapa; Insumran, Yuwadee; Pawala, Thanyachanok; Jumroenpat, Paripon; Kaewlamai, Somboon; Nanposri, Natamon (International Journal of Multidisciplinary in Management and Tourism, 2025)
Experience economy businesses are now using customer-centricity as a fundamental framework for management, which focuses on emotionally engaging personalized experiences instead of standard products or services. The evolution of customer expectations alongside empowered consumers and digital transformation has pushed businesses to become more agile and customer-centered in their operations. The paper examines the strategic development of management practices that focus on customer needs. This research examines the theoretical frameworks and cultural aspects of customer-centricity while exploring enabling technologies and future paths, and compares these elements to conventional product-centered and sales-focused models. The research methodology involves qualitative examination and consolidation of essential literature and theoretical frameworks like Customer Relationship Management (CRM), Service-Dominant Logic, and the Experience Economy. The study examines strategic enablers like leadership and digital tools while utilizing industry examples from Amazon, Apple, Zappos, and Starbucks. The results demonstrate that businesses achieve improved performance through customer-centric strategies, which strengthen customer retention alongside boosting Net Promoter Scores and Customer Lifetime Value. Businesses that combine leadership dedication with the elimination of organizational silos and the implementation of big data and AI technologies succeed in providing uniform personalized customer experiences. Research evidence demonstrates how empathy-driven initiatives combined with employee empowerment and ongoing feedback create lasting brand trust and emotional customer connections. In conclusion, Successful business models now depend on customer-centric strategies that integrate essential elements such as empathy and responsiveness into core business activities and value creation processes. When organizations emphasize these principles, they build stronger customer relationships and create sustainable innovation and market resilience in the experience-based competitive landscape.